Estrogen Withdrawal from Osteoblasts and Osteocytes Causes Increased Mineralization and Apoptosis - Brennan, M. Á.; Haugh, M. G.; O’Brien, F. J.; McNamara, L. M. (Hormone and Metabolic Research, 2014)
Recent studies have demonstrated increased bone mineral heterogeneity following estrogen withdrawal in vivo. Such changes likely contribute to fracture risk during post-menopausal osteoporosis since tissue mineralization is correlated with bone strength and stiffness. However, the cellular mechanisms responsible for increased mineral variability have not yet been distinguished. The objective of this study is to elucidate how alterations in mineral distribution are initiated during estrogen depletion. Specifically, we tested two separate hypotheses; (1) estrogen deficiency directly alters osteoblast mineralization and (2) estrogen deficiency increases bone cell apoptosis. Osteoblast-like cells (MC3T3-E1) and osteocyte-like cells (MLO-Y4) were pretreated with or without estrogen (17β-estradiol) for 14 days. Estrogen deficiency was subsequently induced by either withdrawing estrogen from cells or blocking estrogen receptors using an estrogen antagonist, fulvestrant (ICI 182,780). Cell number (Hoechst DNA), alkaline phosphatase activity (p-NPP), mineralization (alizarin red) and apoptosis (Caspase 3/7) were evaluated. Whether estrogen withdrawal altered apoptosis rates in the presence of an apoptosis promoting agent (etoposide) was also determined. Interestingly, estrogen withdrawal from cells accustomed to estrogen exposure caused significantly increased osteoblast mineralization and osteocyte apoptosis compared with continued estrogen treatment. In contrast, blocking estrogen receptors with fulvestrant abrogated the mineralization induced by estrogen treatment. When apoptosis was induced using etoposide, cells undergoing estrogen withdrawal increased apoptosis compared to cells with continued estrogen treatment. Recognizing the underlying mechanisms regulating bone cell mineralization and apoptosis during estrogen deficiency and their consequences is necessary to further our knowledge of osteoporosis.
Keywords: estrogen deficiency; osteoblasts; osteocytes; mineralization; apoptosis